Analysis of the Effectiveness of LKPD Based on Project Based Learning (PJBL) to Stimulate Students' Critical Thinking - Dayanti, Kris; Khuzaini, Nanang; Febriyanto, Bernard; Gunadi, Syahrul; Fricelaa, Nady (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
Critical thinking skills master the material where students recognize, know, master, and are able to re-express concepts in a form that is easier to understand. However, students' critical thinking skills still tend to be low. So it takes teaching materials that integrate these abilities. For this reason, this study aims to develop Student Worksheets (LKPD) based on Project Based Learning (PjBL) in order to stimulate critical thinking for class VII students on quality triangle and quadrilateral material seen from aspects of validity, practicality and effectiveness. This type of research is descriptive qualitative. This research was conducted in one of the Junior High Schools in Yogyakarta. The subjects in this study were 32 students of class VIIC. Data collection techniques used interviews, concept understanding ability tests, and preliminary questionnaire studies. While the data analysis technique uses the Miles and Huberman model which consists of data collection, data reduction, data presentation, and drawing conclusions. The results showed that teachers had implemented learning assisted by LKPD teaching materials, but students' critical thinking skills tended to be low, students were interested in learning using LKPD which was more interesting because students could develop their way of thinking and make them more active in learning.